The influence of β-amyloid on [18F]AV-1451 in semantic variant of primary progressive aphasia. (12th February 2019) - Whitwell, Jennifer L.; Martin, Peter R.; Duffy, Joseph R.; Clark, Heather M.; Machulda, Mary M.; Schwarz, Christopher G.; Weigand, Stephen D.; Sintini, Irene; Senjem, Matthew L.; Ertekin-Taner, Nilufer; Botha, Hugo; Utianski, Rene L.; et al.
Abstract : Objective: To compare [ 18 F]AV-1451 uptake in the semantic variant of primary progressive aphasia (svPPA) to Alzheimer dementia, and determine whether increased uptake in svPPA is associated with the presence of β-amyloid (Aβ). Methods: Thirty-one participants with svPPA underwent MRI and Pittsburgh compound B–PET scanning, and 17 of these also underwent [ 18 F]AV-1451 tau-PET. A global Pittsburgh compound B standardized uptake value ratio was calculated for all participants, with a cutoff of 1.42 used to define Aβ(+) participants. We assessed region and voxel-level [ 18 F]AV-1451 uptake in the whole svPPA cohort and separately in Aβ(+) and Aβ(−) svPPA groups, compared to 12 Aβ(+) participants with Alzheimer dementia and 170 cognitively normal, Aβ(−) controls. Results: Of the entire cohort of participants with svPPA, 26% were Aβ(+). The Aβ(+) participants were older at scan compared to the Aβ(−) participants. svPPA showed elevated [ 18 F]AV-1451 uptake in anteromedial temporal regions but the degree of uptake was lower than in Alzheimer dementia. After controlling for age, Aβ(+) status in svPPA was associated with significantly higher uptake in all anteromedial and inferior/middle lateral temporal regions, but uptake was still lower than in Alzheimer dementia. Conclusion: Although [ 18 F]AV-1451 uptake is focally elevated in svPPA, the level of uptake is much less than what occurs in Alzheimer dementia and appears to be at least partially related to Aβ. Therefore, it is possible that some of the increased uptake of [ 18 F]AV-1451 in svPPA is related to binding paired helical filament tau.